Patients’ perceived involvement in clinical decision-making and associated factors among adult patients admitted at Jimma Medical Center, Oromia, Ethiopia: a cross-sectional study - Yonas Gurmu Dugasa; Keneni Dina Dibera; Wadu Wolancho Debancho; Gadisa Bekele Bedada (BMJ Open)
Objective To assess patients’ perceived involvement in clinical decision-making and associated factors among adult patients admitted at Jimma Medical Center, Oromia, Ethiopia, 2022.Design An institution-based cross-sectional study was employed.Setting A study was conducted at a governmental tertiary teaching and referral hospital located in Jimma Zone, Oromia region, southwestern part of Ethiopia. The study was conducted between 15 July and 7 September 2022.Participants A total of 422 randomly selected adult patients admitted at Jimma Medical Center were enrolled, after excluding those who were acutely ill during the study period.Methods Data were collected via a structured, interviewer-administered tool, entered into EpiData V.4.6 and exported to SPSS V.26 for analysis. Bivariable and multivariable logistic regression analyses were used to identify factors associated with the outcome variable. Significant factors were declared at p<0.05.Main outcome measure Patients’ perceived involvement in clinical decision-making (adequate involvement/poor involvement).Results A total of 51.4% (95% CI: 46.4 to 56.3) of respondents had adequate perceived involvement in clinical decision-making. Participants who were aged >60 years (adjusted OR (AOR): 2.01 (95% CI: 1.44 to 5.65)), college and above the level of education (AOR: 4.6 (95% CI: 1.6 to 13.26)), length of hospital stay >15 days (AOR: 2.8 (95% CI: 1.41 to 5.5)) and high health literacy level (AOR: 2.04 (95% CI: 1.34 to 4.21)) were more likely to be associated with adequate perceived involvement in clinical decision-making whereas non-prior hospitalisation (AOR: 0.493 (95% CI: 0.3 to 0.82)) and passive autonomy preference (AOR: 0.22 (95% CI: 0.13 to 0.37)) were less likely to be associated with adequate perceived involvement in clinical decision-making than each of their corresponding counterparts.Conclusion Only nearly half of the respondents had adequate perceived involvement in clinical decision-making. Collaborative autonomy preferences, high educational levels, long length of hospital stay, high health literacy level and patients in the older age group were among the factors significantly associated with respondents’ adequate perceived involvement in clinical decision-making. Healthcare professionals have to consider empowering patients’ perceived involvement in clinical decision-making, and hospital management has to reinforce healthcare professionals’ efforts to promote patients’ perceived involvement in clinical decision-making.